A Study of CO Emission Sources and Their Impacts on the Respiratory Systems of Patients in Al-Muthanna Governorate - Farah Ali; Ali Abdulhamza Al -Fanharawi (مجلة علوم ذي قار)
This study examines carbon monoxide (CO) emissions and their health effects on individuals with respiratory conditions such as asthma, COPD, and bronchitis. CO sources include biomass burning, industrial processes, and vehicle exhaust, with CO's high hemoglobin affinity impairing oxygen transport. The current study aimed to assess CO emissions' impact on respiratory health in Al-Muthanna Governorate. From November 2023 to July 2024, CO levels were measured in high-emission areas, including a cement factory, oil refineries, and seven fuel stations, using Drager X am 5000 devices. Two control areas, Hay Al Hussein and Al Doha Residential Compound, were used for comparison.